1985
DOI: 10.1016/0031-9384(85)90146-5
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control in a state of decreased activation: Potentiation of arginine vasopressin secretion

Abstract: PHYSIOL BEHAV 35(4) 591-595, 1985 --Behaviorally induced stress is associated with increased arginme vasopressln (AVP) secretion. In this report we describe a phasic conditioned response of AVP secretion yielding 2.6--7.1 times normal plasma concentration of this hormone m assocmtlon w~th a physmlog~cal state of decreased activation, that associated with the mental technique of "transcendental meditation" (TM) in long-term practltmners (6-8 years of regular elicitation) Such a very large phastc response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The TM subjects of these investigations are longterm practitioners. Whereas the results of early research studying only whole body respiratory change were consistent with physiologic similarity of TM and rest, more recent measurements---specifically on TM subjects who have now been eliciting this behavior for 5-10 years---indicate development of other fundamentally different hormonal, circulatory, and electrophysiologic changes [7,[11][12][13][14]18] in this group. Since participation of a humoral agent(s) in the TMinduced decline of red cell glycolysis is likely [12], it is possible that repeated elicitation or some special feature of this behavior is necessary for elaboration of the responsible effector.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The TM subjects of these investigations are longterm practitioners. Whereas the results of early research studying only whole body respiratory change were consistent with physiologic similarity of TM and rest, more recent measurements---specifically on TM subjects who have now been eliciting this behavior for 5-10 years---indicate development of other fundamentally different hormonal, circulatory, and electrophysiologic changes [7,[11][12][13][14]18] in this group. Since participation of a humoral agent(s) in the TMinduced decline of red cell glycolysis is likely [12], it is possible that repeated elicitation or some special feature of this behavior is necessary for elaboration of the responsible effector.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, the temporal patterns of plasma arginine vasopressin (AVP), oxytocin, growth hormone, and prolactin [ 11,14,18] during TM diminish the likelihood of their participation in this response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have suggested a mutual activation of parasympathetic and sympathetic systems by demonstrating an increase in the variability of heart rate during meditation (Peng et al, 1999). Measures of hormone and immune function have also been explored especially as an adjunct measure to various clinical outcomes (O’Halloran et al, 1985; Walton et al, 1995; Tooley et al, 2000; Infante et al, 2001). Hormonal changes associated with spiritual practices include those to cortisol, noradrenaline, endorphins, sex hormones, and growth hormone (Werner et al, 1986; MacLean et al, 1997; Nidhi et al, 2013; Sooksawat et al, 2013).…”
Section: Objective Measures Of Spiritualitymentioning
confidence: 99%
“…62 Finally, this second prediction also finds support from current studies of alternate nostril breathing, 63 breath-slowing and breath-holding practices, 64 as well as from the emerging consensus that conscious breathing exerts smart-vagal dominance over the primitive sympathetic nervous system (SNS) and PNS, 65 balancing and integrating them to support social engagement with the help of the mammalian neuropeptides vasopressin and oxytocin. 66 Of note, this tradition would weigh in on current discussions of whether the slowing of cortical atrophy by meditation is due to neuroplasticity or to stress protection, predicting that these two mechanisms are linked and synergistic aspects of one general process of lateral integration are employed at all mind/brain levels in different ways by different meditative practices (see Figure 2). Thirdly, the traditional model predicts that there is a central locus of self-regulation at the level of central cardiorespiratory control, that breath is controlled by two binary circuits above and below that level, and that voluntary breathing, breath slowing, and breath holding can help link the circuits, yielding full access and control of primal winds and drops that support motivation and reward as well as the vital rhythms of life.…”
Section: Past History Current Models and Future Directions: A Topicmentioning
confidence: 99%